Epitaxial growth and multiferroic properties of artificial LCMO/BCZT heterostructure on (1 0 0) MgO substrate by pulsed laser deposition. (17th October 2019) - Hu, Mingzhe; Li, Songbin; Wang, Chuanbin
Abstract: Here, we reported the structure, morphology and multiferroic properties of the La0.67 Ca0.33 MnO3 /Ba0.85 Ca0.15 Zr0.9 Ti0.1 O3 (LCMO/BCZT) magnetoelectric epitaxial heterostructure deposited on (1 0 0) MgO single crystal substrate using pulsed laser deposition. XRD RSM confirmed the epitaxial growth of the heterostructure with single oriented grains, and the smooth surface and uniform film growth of the heterostructure were revealed by the AFM analysis. The heterostructure exhibited multiferroic properties with a dielectric constant of 378, a remnant polarization of 10.26 µ C cm −2, a maximum piezoelectric coefficient of 62.5 pm V −1 and a saturated magnetization 814.8 emu cm −3 . The well-shaped ferroelectric and ferromagnetic hysteresis loops verified the multiferroic nature of the heterostructure with a maximum magnetoelectric coefficient α E 31 of 36.9 mV (cm · Oe) −1 .